Effectiveness of Driving the Tourism Attractions Strategy According to the Thai-Way-of-Life Identity. - Sirilapanan, Somsak (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this study were threefold: 1) To investigate the effectiveness of Driving the Tourism Attraction Strategy in Bangkok Metropolitan areas; 2) To determine the guidelines for use in integrating the public sector, the private sector and the civil society with an effort to drive the Tourism Attraction Strategy; and 3) To offer recommendations for and recognition of driving the Tourism Attraction Strategy According to the Thai-Way-of-Life Identity in Bangkok Metropolitan areas. The study was qualitative in nature 22 key informants comprised the sample of the study; the key informants include persons of high caliber from the public sector, the private sector and the civil society. The colueled data were analyzed by means of content analysis. The qualitative data analysis has shed light on the facts specified below. 1. With respect to the effectiveness of Driving the Tourism Attraction Strategy According to the Thai-Way-of-Life Identity; it could be said that driving the Thai economic growth was emphasized. In a sense, the stress was put on the generation of revenues and economic prosperity. To this end, great efforts were made to make planes designed to organize and support a variety of tourism activities as well as to maintain the outstanding strength of Thailand particularly in the dimensions of customs, tradition, culture, as well as Thai identity. Expectedly, the incomes earned from tourism activities would disperse from the capital city to the satellite areas in a sustainable manner. 2. In regard to the guidelines for use in the integration of the public sector, the private sector and the civil society relevant to driving the Tourism Attraction Strategy According to the Thai-Way-of-Life Identity, various agencies from the three sectors introduced new tourism attractions and offered new tourism perspectives. Furthermore, authorities from these agencies encouraged and support the potential tourism attraction rich in same outstanding features and Thai identity by making alliances for the sustainability and quality of tourism attractions as well. 3. Based on the findings of the study, the researcher has made the following recommendations, 3.1. Attempts should be made to develop spaces, tourism facilities and tourism logistics, apart from boosting the tourist’s safety. 3.2. The successful driving of the Tourism Attraction Strategy According to the Thai-Way-of-Life Identity calls for tourism human resource and tourism entrepreneur development in a way that is consistent with the tourism information management system; moreover, some obsolete laws and ineffective law enforcement should be revised. 3.3. All possible efforts should be made to encourage the diversification of geographic and cultural spheres of tourism activities with a view to adding values and enhancing the effectiveness and efficiency of tourism management in Bangkok Metropolitan areas. Article history: Received 2 June 2019 Revised 26 June 2019 Accepted 28 June 2019 SIMILARITY INDEX= 0.00 %